Evaluation of polymerase chain reaction assays for direct screening of carbapenemase-producing Enterobacteriaceae from rectal swabs: a diagnostic meta-analysis. Issue 3 (March 2020) - Saliba, R.; Aho-Glélé, L-S.; Karam-Sarkis, D.; Zahar, J-R.
Summary: Recently, molecular assays have been demonstrated to be reliable for rapid detection of carbapenemase-producing Enterobacteriaceae (CPE) directly from positive blood cultures, reducing significantly the time for identification. Few studies have tested their performance on rectal swabs and no comprehensive conclusions have been reached regarding their utility for infection control management. Our aim was to review and assess the overall diagnostic test accuracy of polymerase chain reaction for the detection of CPE in rectal swabs. The electronic database PubMed was searched, up to October 1 st, 2019, without language restriction or publication date restrictions. First, the concepts of the research questions were defined: 'carbapenemase-producing Enterobacteriaceae', 'molecular testing', 'test detection', and 'rectal screening'. Two reviewers independently screened studies, extracted data, and assessed quality using the QUADAS-2 instrument. Statistical analyses were carried out in Stata software using the bivariate model. In all, 143 articles were screened and 16 studies were included. Five (31%) of the studies were conducted in the context of a CPE outbreak; one study (6%) included patients pre-identified with CPE in clinical samples (blood or tracheal secretions), whereas the rest (63%) collected rectal swabs from patients considered at high risk of colonization. The molecular assays evaluated had a relatively good sensitivity of 0.95 (95% confidence interval (CI): 0.902–0.989), and an excellent specificity of 0.994 (95% CI: 0.965–1). Molecular techniques seem to be a useful, accurate diagnostic tool in screening for carriage of CPE in contact patients around a fortuitous discovery of a non-isolated hospitalized carrier patient.